UPAYA MENINGKATKAN KEMAMPUAN SELF CONTROL PADA ANAK MELALUI BERCERITA - Maulida Nur; Neni Farida (Jurnal Anak Bangsa, 2022)
The purpose of this study is to increase the ability of self-control in children in group A at Al Mustaqim Kindergarten because there are still children in group A that are still lacking. Self-control is one of the emotional developments that need to be built since children are still small. Self-control is a person's ability to control himself so that his behavior is not detrimental to himself or to others. Self-control is also defined as the human capacity to control the response. Children must be taught self-control from an early age so that they are able to make their own choices in acting and take responsibility for their actions. This study uses a qualitative approach with classroom action research (CAR) methods and uses the Spiral model from Kemmis and Taggart. Based on observations in various aspects of the use of the storytelling method, it has been shown that the ability of self-control in cycle 1, cycle 2 and cycle to have shown a significant increase